2006
DOI: 10.1007/s00430-006-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lysostaphin in HeLa cells protects from host cell killing by intracellular Staphylococcus aureus

Abstract: The Staphylococcus aureus-specific cell wall endopeptidase lysostaphin was used as a model for an intracellular acting bactericidal antibiotic. HeLa cells were transfected with an expression vector directing the heterologous expression of lysostaphin in the cytoplasm. Expression, subcellular localization and enzymatic activity of lysostaphin were investigated by immunoblotting, fluorescent microscopy and agar diffusion assays. Both transiently and stably transfected HeLa cells showed a strong expression of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The RNAIII effector molecule of the agr locus, which encodes δ-toxin, has been reported to be a key factor in S. aureus -induced cytotoxicity (Shompole et al , 2003). δ-toxin has been shown to possess cytolytic properties (reviewed in (Verdon et al , 2009)), and has been suggested to mediate phagosomal escape by S. aureus (Giese et al , 2011, Shompole et al , 2003), a proposed prerequisite for induction of host cell death (Klein et al , 2006). We found that agr null mutants caused approximately 20% less EC damage than did their respective parental strains.…”
Section: Discussionmentioning
confidence: 99%
“…The RNAIII effector molecule of the agr locus, which encodes δ-toxin, has been reported to be a key factor in S. aureus -induced cytotoxicity (Shompole et al , 2003). δ-toxin has been shown to possess cytolytic properties (reviewed in (Verdon et al , 2009)), and has been suggested to mediate phagosomal escape by S. aureus (Giese et al , 2011, Shompole et al , 2003), a proposed prerequisite for induction of host cell death (Klein et al , 2006). We found that agr null mutants caused approximately 20% less EC damage than did their respective parental strains.…”
Section: Discussionmentioning
confidence: 99%
“…CFT-1, LCFSN RN6390 IF (Jarry and Cheung, 2006) Reduced proportion of LAMP-positive phagosomes in CFT-1 at 2 and 4 h, as opposed to LCFSN HeLa ATCC29213 Lysostaphin expression in host cells (Klein et al, 2006) Reduced whereas multiple virulence factors are down-regulated. When investigating phagolysosomal localisation of S. aureus by IF for lysosomal markers such as LAMP-1, LAMP-2, etc., ring-like structures can be detected surrounding the staphylococci.…”
Section: Pitfalls Investigating the Fate Of Intracellular S Aureusmentioning
confidence: 97%
“…It has been suggested as early as 1998 that S. aureus escapes the phagosomal compartment in non-professional phagocytes (Bayles et al, 1998). Phagosomal escape of S. aureus seems to be a prerequisite for induction of host cell death, since the glycyl-glycyl endopeptidase lysostaphin expressed in the cytoplasm of HeLa cells protected HeLa from induction of host cell death by internalized S. aureus ATCC29213 (Klein et al, 2006) and since only invasive and haemolytic strains induce apoptosis in human endothelial cells (Haslinger-Löffler et al, 2005).…”
Section: Phagosomal Escape and Role Of S Aureus A-toxinmentioning
confidence: 99%